1985
DOI: 10.1111/j.1471-0528.1985.tb01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal azathioprine therapy and depressed haemopoiesis in the babies of renal allograft patients

Abstract: Maternal immunosuppression with azathioprine during prcgnancy can depress fetal haemopoiesis resulting in neonatal thrombocytopenia and leucopenia with the potential for serious sequelae. The effect on the infant of adjusting azathioprine dosage on the basis of maternal total leucocyte count has been studied in 10 pregnancies in eight renal allograft recipients. Throughout the first six pregnancies azathioprine dosage was unchanged and although the characteristic pregnancy leucocytosis was evident it was not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(42 citation statements)
references
References 21 publications
0
40
1
1
Order By: Relevance
“…These neonates were clinically asymptomatic in 12/13 cases, but the immunomonitoring of children exposed to AZA is recommended [37]. Other reported adverse effects are decreased thymic shadow, anemia, reduced immunoglobulin levels, infections and septicemia, chromosomal abnormalities that may persist for up to 1 year, as well as sequelae from preterm delivery and IUGR [4,36].…”
Section: Aza 6-mpmentioning
confidence: 99%
See 1 more Smart Citation
“…These neonates were clinically asymptomatic in 12/13 cases, but the immunomonitoring of children exposed to AZA is recommended [37]. Other reported adverse effects are decreased thymic shadow, anemia, reduced immunoglobulin levels, infections and septicemia, chromosomal abnormalities that may persist for up to 1 year, as well as sequelae from preterm delivery and IUGR [4,36].…”
Section: Aza 6-mpmentioning
confidence: 99%
“…AZA presents with teratogenicity in animal studies, with a high incidence of embryonic resorption and fetal anomalies [34,36]. However, it does not seem to be teratogenic in humans, even if there were isolated case reports of fetal malformations, including craniosynostosis, hypoplasia of the frontal lobe and ventriculomegaly [3].…”
Section: Aza 6-mpmentioning
confidence: 99%
“…49 The level of 6-TGN is associated with myelosuppression in adults, and may rarely prompt transient myelosuppression after in utero exposure. 50 Series of pregnancies exposed to azathioprine for inflammatory bowel disease or renal transplants show no significant increase in fetal abnormalities. 47 Among renal transplant patients, however, up to 40% of the offspring were small for gestational age.…”
Section: Prevention Of Sle Activitymentioning
confidence: 99%
“…Risks of other adverse pregnancy outcomes such as intrauterine growth retardation, prematurity (Goldstein et al 2007;Armenti et al 2002;Pirson et al 1985), and immunosuppression (Alter 1985;Davison et al 1985;DeWitte et al 1984;Sahasranaman et al 2008) have been reported, although these may be the results of the disease itself.…”
Section: Thiopurinesmentioning
confidence: 93%